343 A Systematic Review of Symptomatic Hamartomas of The Jejunum and Ileum. (4th May 2021) - Conroy, M; Farkas, N; Baig, M
Abstract: Introduction: Gastrointestinal hamartomas are rarely encountered benign growths made of an abnormal mixture of tissues normally found in the body where the growth occurs. Most hamartomas are asymptomatic and diagnosed incidentally. Evidence regarding symptomatic hamartomas of the jejunum and ileum is limited. Method: The search terms 'small bowel, ' 'small intestine, ' 'jejunum' and 'ileum' were combined with 'hamartoma.' EMBASE, Medline, PubMed searches and Google Scholar hand searches were conducted. All English language papers from 01/01/2000-01/06/2020 were included. Results: A total of 39 cases were reviewed, 29 adults and 10 paediatric (0-16 years). Presenting symptoms included: abdominal pain (87%), vomiting (56%), gastrointestinal bleeding (20.5%) and weight loss (5%). Stricturing was noted in 7 cases. 36/39 (92%) presented as emergencies. Diagnostic investigations included: Abdominal X-ray (49%), endoscopy (38%) and CT (56%). Initial management strategy was either open (30) or laparoscopic (7) surgery or endoscopy (2). All cases required surgery for definitive management. 9/39 cases were associated with hamartomatous syndromes. 2 mortalities were recorded. Conclusions: This is the first review addressing symptomatic hamartomas of the jejunum and ileum. New data relating to demographic cohort, symptom profile, investigations, management strategies and morbidity and mortality provide greater insight to those encountering this challenging clinical finding in the future.